Internações evitáveis pela atenção primária à saúde em um município da região central do Brasil - (:unkn) unknown (Universidade Federal de Goiás, 2017)
Primary care stands out globally in health care and its performance is verified through the analysis of the indicator of Hospitalizations for Primary Care Sensitive Conditions (ICSAP) that could be avoided or reduced in frequency by a quality service. Therefore, the objectives of the research were: to verify if with the increase of FHT there was a reduction in the number of ICSAP and the costs of the same in a municipality of the Central Region of Brazil between the years 2010 to 2014. It is an ecological study of Descriptive character classified as an observational study. Data collection was performed from April 1 to May 31, 2016. Secondary information obtained through data records collected through the Hospital Information System based on the Hospital Inpatient Authorization was used. After approval by the Research Ethics Committee, the Software Tab for Windows - TabWin version 3.5 - was applied for data extraction. The information was then tabulated in Excel spreadsheets and the statistical program Statistical Package Social Sciences - SPSS, version 20.0 for the codification and separation of hospitalizations for Primary Care Sensitive Conditions. It was observed that, during the study period, 24,462 hospitalizations occurred, of which 6,559 were due to conditions sensitive to primary care, corresponding to 26.93% of all hospitalizations. The total expenses with general hospitalizations were R $ 17,760,033.75, while R $ 1,823,208.13 financed the hospitalization for sensitive conditions. The most frequent causes were: volume depletion, congestive heart failure, urinary tract infection without specification, stroke without ischemic or hemorrhagic discrimination, diarrhea and gastroenteritis of infectious origin. The highest frequency occurred in the age group of 60 years of age or older, with a higher proportion for males in this population. For the other age groups, the female sex was the most internalized. The indicator was an important instrument, identifying the main sensitive causes that require intervention through more effective actions by the primary care with the objective of preventing and reducing hospitalizations, increasing the quality of life.
Avoidable interactions for primary health care in a municipality of the central region of Brazil
Keywords: Atenção primária à saúde; Avaliação de serviços de saúde; Gestão em saúde; Hospitalização; Políticas de saúde; Primary health care; Evaluation of health services; Health management; Hospitalization; Health policies; ADMINISTRACAO::ADMINISTRACAO DE SETORES ESPECIFICOS